Comparison of Land Law Systems: A Study on Compensation Arrangements and Reappraisal of Land Acquisition for Public Interest between Indonesia and Malaysia - Sari, Embun; Yamin, Muhammad; Purba, Hasim; Sembiring, Rosnidar (International Journal of Criminology and Sociology, 2021)
Land is a livelihood land for everyone to achieve prosperity in various fields; besides that, the land is also the essential capital in the development of a nation, and its benefits must be exploited as well as possible. There are still many lands affected by the procurement of development for the public interest that are detrimental to the community, including compensation and land that an appraisal has not appraised. This research method uses normative juridical research with the approach of laws and concepts and collects primary legal materials in existing regulations in both countries. Data collection techniques consist of literature study, observation, interviews, and use of questionnaires. The results of this study found that both Indonesia and Malaysia regulate compensation arrangements in the Act. Although both of them depart from different legal systems, where Indonesia is subject to the civil law system and Malaysia is subject to the common law system, both have the same. In Indonesia, it has not explicitly regulated reappraisal in its law, in the future, it is necessary to consider the pattern of reappraisal carried out by Malaysia, because this pattern according to the author, with the current legal vacuum, it is necessary to have a fast track process to provide justice and legal certainty.